Weak versus strong knowledge interdependence: A comparison of two rationales for distributing information among learners in collaborative learning settings. (December 2015) - Deiglmayr, Anne; Schalk, Lennart
Abstract: Traditional jigsaw-type scripts create strong knowledge interdependence by distributing information on core concepts between learners. However, previous research indicates that such knowledge interdependence may hinder interactive knowledge co-construction by reducing learners' common ground on core concepts. In an experiment with undergraduates (n = 78) in three-person-groups, we contrasted two rationales for distributing information: (1) establishing strong knowledge interdependence by distributing knowledge on core concepts as in a traditional jigsaw-type script, and (2) establishing weak knowledge interdependence by distributing only contextual information in a modified jigsaw-type script. Weak knowledge interdependence particularly benefitted low prior knowledge learners' transfer performance. Furthermore, it supported learners' interactive knowledge co-construction during collaboration, and this interactive co-construction mediated the effects of knowledge interdependence on individual learning. This study illustrates how collaborative and individual learning activities interrelate, and that a slightly modified jigsaw-type script makes a valuable addition to an instructor's toolbox. Highlights: Jigsaw-type scripts should ensure common ground on core concepts among learners. Weak (vs. strong) knowledge interdependence (KI) ensures such common ground. Weak KI was more effective for low prior knowledge learners. Weak KI benefitted interactive knowledge co-construction and individual transfer. Interactive co-construction mediated between degree of KI and individual learning.